EMPLOYEE PERFORMANCE OPTIMIZATION REVIEWED FROM COMPETENCY AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) - Wachyu Hari Haji; Meiliyah Ariani; Islamiah Kamil (ZILLZELL MEDIA PRIMA, 2024)
Every organization is required to be able to optimize human resources and how these human resources are managed. Therefore, an organization must be able to organize all existing human resources so that organizational activities can run smoothly and be able to compete with its competitors. One of them is to consider based on the competencies and organizational citizenship behavior (OCB) owned by employees. The purpose to be achieved in this study is to prove that the performance of PT Biantara Jaya Service employees can be optimized through competency variables and Organizational Citizenship Behavior (OCB). The type of research used in this research is quantitative research. The type and source of data used in this study are primary data. The data collection method in this study uses a population questionnaire and the sample in this study is 40 respondents of PT Biantara Jaya Services employees and all of them are used as saturated samples. The data analysis in this study used multiple linear regression using validity test, reliability test, multiple linear regression analysis test and t hypothesis test and determination coefficient test with the SPSS 26 For Windows statistical application program. The results of the research that have been conducted show that employee competence measured through knowledge, expertise/skills, and attitudes has a positive and significant effect on performance. Likewise, the organizational citizenship behavior (OCB) variable which is measured through the accuracy of task completion, attendance level, cooperation, and job satisfaction has a positive and significant effect on performance.